Perbandingan Efektivitas Google Meet dan Zoom Berdasarkan Pengalaman Mahasiswa dalam Proses Pembelajaran Daring - Martyani, Eka; Yamalia, Ikke (Nolsatu Publisher, 2025)
Since 2019/2020, video conferencing has become increasingly popular, especially since the Covid-19 pandemic restricted face-to-face meetings. Platforms like Zoom and Google Meet have become important alternatives to support long-distance communication, including in education, which greatly requires direct interaction in the teaching and learning process. Both applications are popular among lecturers and students because they can support online lectures. Zoom and Google Meet each have their own advantages and disadvantages, both in terms of features, duration of use, functionality, and ease of access. Zoom is better known for its comprehensive interactive features such as breakout rooms and virtual backgrounds, while Google Meet excels due to its simplicity, ease of access, and integration with other Google services. The increasing demand for video conferencing has led to the increasing use of these two platforms in academic activities. This study aims to compare student experiences in using Zoom and Google Meet. Data was collected from students at University [X] who attended online lectures over the past two semesters. The results indicate that Zoom is preferred for interactive lectures, while Google Meet is more stable and easier to access. These findings are expected to inform educational institutions' considerations in determining the platform that best suits the needs of lecturers and students.